Varma modelling for window size and RTT in TCPIP networks - Li, Yingzi (University of Ottawa (Canada), 2004)
TCP (Transmission Control Protocol) and IP (Internet Protocol) are the most important protocols used for most of the data transmission across the Internet. Modern implementations of TCP mostly involve the concepts of Window Size and Round Trip Time (RTT) in controlling network congestion. We model simulated time series of Window Size and RTT to evaluate the characteristics and the relationship of the data over time using autoregressive moving average methods. These methods help us to forecast network performance and detect server congestion.
Keywords: Mathematics.; Computer Science.